PENGELOLAAN PEMBELAJARAN MATEMATIKA MODEL PAIKEM PADA SISWA MADRASAH IBTIDAIYAH - Makinem Makinem (Manajer Pendididikan, 2015)
This study includes learning management PAIKEM models in mathematics. The method used is a class action research. The subjects were students of class V MI Nurul Huda of Bengkulu. Data collection technique used tests, observation and documentation. Results of the study are: an increase in the average percentage of students' learning activities from 73.05% to 77.34%. Average increase learning outcomes of 66.65% with a percentage thoroughly studied classical 60.53% to 76.12% with the percentage of 81.58% complete classical learning. Teacher performance of the average value of 78.28 increased to 82.74. So it can be concluded that the learning management PAIKEM models can increase the activity and student learning outcomes and teacher performance in mathematics.Keywords: mathematics, PAIKEM, management